1990
DOI: 10.1002/em.2850160502
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of four in vitro genetic toxicity tests for predicting rodent carcinogenicity: Confirmation of earlier results with 41 additional chemicals

Abstract: The effectiveness of four in vitro short-term tests (STT) for genetic toxicity, induction of mutations in Salmonella (SAL) and mouse lymphoma L5178Y cells (MLA), and induction of sister chromatid exchanges (SCE) and chromosome aberrations (ABS) in Chinese hamster ovary cells that are used for predicting rodent carcinogenicity were examined. The in vitro results were compared with the results from 41 rodent carcinogenicity studies performed by the National Toxicology Program. The predictive values of, and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(79 citation statements)
references
References 28 publications
(19 reference statements)
3
75
0
1
Order By: Relevance
“…assay, 67% for SCE induction and 66% for the mouse lymphoma assay. Similar results, which confirmed that Salmonella is the most predictive for carcinogenicity, were obtained by Zeiger et al [32]. In a comparison of results from in vitro clastogenicity assays and evaluation of carcinogenicity, Ishidate et al [11] found that among 165 clastogens, 91 (55%) were carcinogens and 56 (34%) were chemicals which had shown some indications of carcinogenicity.…”
Section: Discussionsupporting
confidence: 74%
“…assay, 67% for SCE induction and 66% for the mouse lymphoma assay. Similar results, which confirmed that Salmonella is the most predictive for carcinogenicity, were obtained by Zeiger et al [32]. In a comparison of results from in vitro clastogenicity assays and evaluation of carcinogenicity, Ishidate et al [11] found that among 165 clastogens, 91 (55%) were carcinogens and 56 (34%) were chemicals which had shown some indications of carcinogenicity.…”
Section: Discussionsupporting
confidence: 74%
“…The results obtained for the 41 chemicals were similar to those reported for the 73 chemicals (12). No significant differences between the two datasets were detected and hence the two datasets were combined into a single dataset of 114.…”
Section: Introductionsupporting
confidence: 77%
“…Approximately one-third of nonmutagenic chemicals are carcinogenic, and approximately one-third of the mutagenic chemicals are noncarcinogenic in the 2-year rodent bioassay (14,15). It has been proposed that chemicals that induce tumors in two rodent species are less influenced by the genetic variability among different species than chemicals that induce tumors in only one species (16).…”
Section: Introductionmentioning
confidence: 99%